The struggle between the constitution and tyranny during the government of Mirza Ahmad Khan, the Field Marshal of the Second Sultanate of Iran1908-1909 - Maytham Hashem Hussein; Majid Abdel Zahra; Kawther abdulhasan abdulha (Zien Journals, 2021)
The period during which Mirza Ahmed Kham, the Mushir of the Sultanate, became prime minister in Iran constituted a major conflict as a result of the political, economic, and social transformations that the country witnessed, the extent of which was not limited to Iran only, but also transcended those borders, to include the regional neighborhood, and to the period in which it was These transformations represent the beginning of the end for him assuming his ministerial portfolio in Iran, and a catalyst in many subsequent events in the political arena, which in turn were also reflected in the general scene in Iran. Given the importance of these events and their political connections that almost constituted a crossroads in the political future of Iran, and the size of their impact on social awareness in Iran, the title of the research came to shed light on the political developments and the accompanying events and conflict between the advocates of the constitution and the oppressive group in Iran during the government of Mirza Ahmad Khan Mushir The second sultanate, as the study was divided into three sections, the first topic dealt with political developments and their effects on the nature of constitutional life. In contrast, the second topic touched upon the Shah’s preparations to strike the National Assembly, while the third topic discussed the stage of petty tyranny.
Keywords: discussed; sultanate; research; political developments